INSPIRATIONAL DA’WAH FOR MILLENNIAL GENERATION: STUDY AT IAIN TULUNGAGUNG - Ahmad Nurcholis; Syaikhu Ihsan Hidayatullah; Izzatul Laila (Jurnal MD, 2019)
The millennial’s interest towards Islamic da’wah is decreased significantly, caused by the da’wah approach and strategy which are still conservative, monotonous, and only delivered on lecturing way. In fact, on the other hand, the millennial generation expects an inspirational, modern, elastic, dynamic, innovative, and entertaining da’wah. This study aims to describe, analyze, and interpret the implications of inspirational da’wah conducted by the Da’wah Management department of IAIN Tulungagung in increasing the young generation's interest in Islamic teachings and da’wah. In principle, inspirational da’wah has been carried out by Suryadharma Ali, the Minister of Religion of the Republic of Indonesia on 2009-2014, who stated that one of the main jobs of UIN and IAIN is to maintain and develop scientific traditions in the field of Islamic studies which are increasingly less desirable by the community because there has been a change in community orientation toward Islamic da’wah. So, the quality of Islamic institutions in Indonesia needs to do the more serious, systematic, and measurable efforts in order to increase the quality of Islamic da’wah, as well as PTKIN graduates must be more competitive. The ideas of this article inspired by the Grand Theory of Medan Da’wah promoted by K.H. Ahmad Muwafiq that the success of the da’wah is influenced by the theological, cultural, and object of the da’wah when the implementation of the Islamic da’wah is delivered. Furthermore, the Islamic da’wah is an inspiration to realize the teachings of Islam in personal and social life in line with the culture of the society in terms of life that aim to uphold amar ma'ruf and nahi munkar. This is qualitative research with a descriptive method of phenomenological analysis. While the results of the study are: First, Inspirational da’wah has implications for increasing trends and millennial generation interest for IAIN Tulungagung students towards Islamic da’wah. Second, the inspirational da’wah referred to in this study is the iain tulungagung hijaber community, inspirational da’wah comedy, electronic da’wah bulletin, da’wah literacy, and online da’wah through the official campus website. Keywords: Inspirational Da’wah, Millenial Generation, IAIN Tulungagung